Respuestas

  • Usuario de Brainly
2013-02-17T00:17:07+01:00

Resolvemos :

Sucesión aritmética :  (1/3) , (2/3) , 1 , (4/3) , (5/3) ...

Datos :                              Fórmula : an = a1 + (n-1)*r

a1 = (1/3)                                               an = (1/3) + (n-1)*(1/3)

r = (2/3)-(1/3) = (1/3)                              an = (1/3)+(n-1)/3

an = ?                                                         an = (1+n-1)/3

a6 = ?                                                         an = n/3   ----> término n- ésimo.

  Ahora hallemos el a6 :

an = n/3

  a6 = 6/3

     a6 = 2

SaLuDos  :)'